Analisis Lingkungan Kerja, Karakteristik Lingkungan Kerja, dan Kemampuan Kerja Pegawai Pada Kantor Kecamatan Wertamrian Provinsi Maluku - Leborius Samangun; Sita Yubelina Sabandar; Manuel August Todingbua (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
The synergy of the work environment, environment characteristics, and comfortable workability will provide work motivation for employees in providing services to the community. The purpose of this study was to analyze the work environment, characteristics of the work environment, and workability of employees at the Wertamrian District Office, Maluku Province. The type of research used was descriptive qualitative. Data collection techniques through interviews with several informants and conducting observations and documentation to support the validity of the information. The results of the study showed that the work environment, characteristics of the work environment, and workability, had an impact and synergy of employees in providing services.